Promoting Speaking Skill through Engage-Study-Active for Indonesian Vocational Students - Yuniasih, Dewati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to illustrate the use of the engage study active, adapted from Harmer (2007) and the conventional teacher-centered method at vocational school in Lampung, Indonesia. Researchers used quasi-experiments using an experiment and a control class with a sample of 73 students. The results of the sample paired t test statistics show that there is a sharp difference between the uses of the two teaching methods. Teaching with English study active can enrich students' vocabulary, increase student motivation, and make the learning process more active.